Pengaruh Terapi Bekam Terhadap Kadar Kolesterol Pasien Hiperkolesterolemia Di Thibbun Nabawi Centre RSIA Zainab Pekanbaru Tahun 2019 - Isnaniar; Wiwik Norlita; Dikki Irma Wiradinata (LPPM Universitas Muhammadiyah Riau, 2020)
One of the treatment that is recommended by the Prophet Muhammad is to bekam . The research is aimed to effect of therapy of cupping to the levels of cholesterol hypercholesterolemia in Tibbun Nabawi Center RSIA Zainab Pekanbaru with the design of the study . non- experimental cross sectional descriptive study, design This is a design study that the observations made are simultaneously at a time ( all the time). Samples of research this is 53 the respondents were drawn based on the criteria of inclusion using techniques nonprobality sampling the types of purposive sampling. Tools measure that is used is the data of patients whobruise in the year 2018. The analysis that is used is the analysis of univariate to determine the distribution of frequencies and bivariate using test Wilcoxon . Results of the study show from 53 people respondents who experienced hypercholesterolemia . as many as 14 people experienced adecrease. The results of the test statistic obtained results are significant with p value (0.000 ) < α (0.05),so it can be concluded that the cupping effect to decrease the levels of cholesterol in the blood in patients with hypercholesterolemia . It is expected that the community could use the therapy of cupping to overcome the diseasehypercholesterolemia . And can be concluded that the therapy cupping effect to decrease the levels of cholesterol in the blood in patients with hypercholesterolemia in Tibbun Nabawi Center.